Compartmentalized bioencapsulated liquefied 3D macro-construct by perfusion-based layer-by-layer technique - Praveen, S. (2015)
Self-supporting, millimeter length 3D constructs consisting of individualized liquefied compartments, were produced using cell encapsulated hydrogel beads as building blocks. A perfusion-based layer-by-layer approach was used that allowed bioencapsulated beads to assemble, pattern, hold and attach to produce non-liquefied 3D constructs with controlled shape, displaying the binding feature of a continuous nanometric multilayer coating. No binders or crosslinking strategies were used. The internal microenvironment of this 3D construct was modified from solid to liquefied state by chelation. MTS and liveâ dead assays showed enhanced L929 cell viability with liquefied 3D constructs, compared to non-liquefied ones. The proposed technique opens new prospects to create complex 3D polyelectrolyte based constructs for tissue engineering applications.